(untitled) (International Journal of Engineering and Computer Science, 2018)
With far reaching utilization of Internet and other correspondence advances, it has ended up to a great degree simple to imitate, impart, and appropriate computerized substance. Accordingly, validation and copyright insurance issues have emerged. Content is the most widely utilized medium going over the Internet other than picture, sound, and feature. The real piece of books, daily papers, website pages, promotion, exploration papers, authoritative reports, letters, books, verse, and numerous different records is essentially the plain content. Copyright insurance of plain content is a huge issue which can’t be approved. The current answer for watermarking of plain content archives are not powerful towards irregular altering assaults and are inapplicable for various spaces. In this paper, we have clarified content watermarking and its different systems.